Analysis Of The Application Of Food Cost Control With Cost Volume Profit Analysis To Optimize The Profit Of Ocean Garden Restaurant - Dyatri Utami Arina Absari (International Journal of Economic Research and Financial Accounting, 2023)
in order to obtain optimal profit by not neglecting the quality and quantity of the presented menus, (2) know the percentage of food cost compared to the selling price of best seller menu at Ocean Garden Restaurant, and (3) know the selling price of best seller menu at Ocean Garden Restaurant which had been adjusted to the actual food cost standard in order to optimize the profit by using CVP analysis. This research was a case study and was conducted at Ocean Garden Restaurant, Trunojoyo, Malang. The data were analyzed by describing food cost, food percentage, contribution margin, and selling price. Based on the research findings, it was found that the cause of the high food cost was the ineffective food cost control process and food production control and the increase of raw material price that always fluctuated and did not followed by the increase of the selling price. Based on the calculation on the average food cost and average contribution margin, it was found that Ocean Garden’s food cost had a higher value so it required further review and control by the restaurant management.